Development of an extraction method for the determination of inorganic anions (chloride, sulfate and phosphate) in edible oils from different origins by ion chromatography - Fernández Campos, Adriana (2018)
The present work reports the development of ion chromatography conductivity based detection analytical method for the determination of some inorganic anions (chloride, sulfate and phosphate) in vegetable oils. The analytes were extracted from samples prior to injection into the chromatographic system, employing a simple two-step procedure. In the first step, 4.5 g of the sample was vigorously mixed with 15 mL of deionized water and then mixed for 15 min on a horizontal roller. Afterwards, the mixture was sonicated for 15 min in an ultrasonic bath. Then, the mixture was centrifuged for 15 min at 5000 rpm and, after filtration through a 0.22 μm membrane, the aqueous phase was used for the determination of the analytes. A clean-up step was introduced in the analysis of olive oils in order to correct an increase of the baseline of the chromatograms. The limits of detection and quantification of the proposed method were, respectively, 0.005 and 0.02 μg g-1 for chloride, 0.02 and 0.06 μg g-1 for phosphate and 0.008 and 0.03 μg g-1 for sulfate. Vegetable oils from corn, canola, soybean, sunflower and olive were analyzed and recovery tests (94.8 ± 10.1% mean recovery) were performed to attest the accuracy of the proposed method.